Pengembangan Card Sort Berbasis Wordwall Materi Siklus Hidup Hewan Meningkatkan Self Esteem dan Literasi Sains Siswa Kelas 3 - Khoiril Mutoharoh; Mohamad Fatih; Ragil Tri Oktaviani (Journal of Practice Learning and Educational Development, 2026)
This research aims to develop IT-based learning media. Learning media has not been maximally appliedfor effectiveness during the learning process. The researcher develops a card sort learning media basedon Wordwall with the topic of animal life cycles. This research aims to improve students' self-esteemand science literacy. In designing the card sort based on Wordwall, the Research and Developmentmethod is applied. The development process follows the ASSURE model, which consists of six stages:student analysis, target determination, method selection, media and material selection, media andmaterial application, encouraging student participation, and finally evaluation and revision. The topicand source of this research are 3rd-grade students at SDN Tumpang 02 in Blitar Regency. Data collectiontechniques consist of observation, interviews, documentation, questionnaires, and tests. Data analysistechniques use normality tests, homogeneity tests, paired sample t-tests, N-gain tests, and MANOVAtests assisted by SPSS 25. The results of the hypothesis test are obtained from the paired sample t-testwith a sig value (2-tailed) of 0.000 < 0.05 with a t-count of -5.671. The N-gain test result is 0.68, and theMANOVA test result is 0.999 > 0.096. Interviews, recordings, and surveys from experts in the media,material, and language sectors are used to collect information. Validation of self-esteem and scienceliteracy improvement is crucial. The validation process in this development involves three validatorsrepresenting the three fields, resulting in a media expert validator with a percentage result of 87%, amaterial expert validator with a percentage result of 97%, and a language expert validator with apercentage result of 90%. All three results fall into the "very valid" category.